Penentuan Indikator Umur Simpan Minuman Botanikal Berbahan Dasar Jahe Merah dan Bawang Putih - Nabila Lathifah Fatmawati; Setya Budi Muhammad Abduh; Ahmad Ni'matullah Al-Baarri (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2023)
Botanical beverages are made from plant extracts that can be packaged to extend their shelf-life. The shelf-life of foods and beverages can be estimated by mathematical modelling, usually by employing linear equation model. To accurately estimate the shelf-life, it is necessary to determine the indicators. This study aimed to determine the shelf-life indicators of a botanical beverage made from red ginger and garlic which were prepared under boiling condition and packaged in glass bottles at hot condition. The product was stored at 27, 33, and 40°C and their quality attributes comprising sensory, visual consistency, viscosity, pH, and total microbe were observed weekly. The data obtained were mathematically modeled using linear equations to determine the order of the reaction (n) and the rate constant (k) of the change in quality attributes. The coefficient of determination (R2) for the equation of change in quality attributes at 27, 33, and 40°C were 0.19, 0.21, 0.62; 0.10, 0.01, 0.01; 0.02, 0.19, 0.89 respectively for viscosity, pH, and total microbe. The total microbe is the most appropriate quality indicator for estimating shelf-life of this botanical beverage.